Vom offenbaren und verborgenen Gott Studien zur spätbiblischen Weisheit und Hermeneutik - Kaiser, Otto 1924-2017 (Berlin [u.a.] De Gruyter, 2008)
The present volume contains writings by the renowned Marburg Old Testament scholar Otto Kaiser on the theology, anthropology and ethics of the Book of Ecclesiastes, or Kohelet, and on The Wisdom of Jesus, Son of Sirach (Ecclasisticus) and its background in the history of ideas and of theology. In addition there is an essay on topical problems of the history of salvation and one on present-day problems of the belief in eternal life
Glaube und Geschichte. Das neue Bild der Vorgeschichte Israels und der christliche GlaubeDer biblische Weg zum Glauben an das ewige Leben; Nachwort; Backmatter
Description based upon print version of record
In German
Keywords: Wisdom Literature -- Criticism, interpretation, etc; Wisdom Literature; Ewiges Leben; Heilsgeschichte; Jesus Sirach; Kohelet; RELIGION / Biblical Criticism & Interpretation / Old Testament; RELIGION / Bible / General; RELIGION / Ancient; RELIGION / General; Eternal Life; History of Salvation; Sirach (Ecclesiasticus); Kohelet (Ecclesiastes); Electronic books; Aufsatzsammlung